Stress coping models and COVID-19 - Guo, PhD, LRT/CTRS, Lei; Yan, PhD, CCC-SLP, Ruixia (American Journal of Recreation Therapy, 2021)
COVID-19 has negatively affected community life and resulted in a significant increase in mental health problems and decreased general well-being. Stress related to COVID-19 worsens mental health problems, especially for those with preexistent conditions. Studies found that people used coping strategies such as hoping for the best, distraction, solving the problem, or seeking emotional and social support during this stressful situation. Stress models including response model, stimulus model, and transactional model from previous studies were introduced to provide more insight on how to cope with stress for the pandemic. Two unique leisure stress coping models, leisure buffering model and hierarchical dimensions model of leisure stress coping were explained as well.